2022
DOI: 10.3390/ma15124069
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Hazards and Natural Radionuclide Distribution in Granitic Rocks of Homrit Waggat Area, Central Eastern Desert, Egypt

Abstract: Natural radioactivity, radiological hazard, and petrological studies of Homrit Waggat granitic rocks, Central Eastern Desert, Egypt were performed in order to assess their suitability as ornamental stone. On the basis of mineralogical and geochemical compositions, Homrit Waggat granitic rocks can be subdivided into two subclasses. The first class comprises granodiorite and tonalite (I-type) and is ascribed to volcanic arc, whereas the second one includes alkali-feldspar granite, syenogranite, and albitized gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…According to the worldwide average concentrations (35, 35, and 400 Bqkg-1) for 226 Ra, 232 Th, and 40 K, respectively, which were reported by [ 40 ], our findings demonstrate that the samples’ average value of 40 K under investigation is lower than the world average, while the average value of 226 Ra and 232 Th are higher than the world average concentrations [ 2 , 41 44 ]. The variations in the activity concentration are associated with the methods by which the soils are concentrated as well as the radioactive distribution in the rocks from which they arise.…”
Section: Resultssupporting
confidence: 61%
“…According to the worldwide average concentrations (35, 35, and 400 Bqkg-1) for 226 Ra, 232 Th, and 40 K, respectively, which were reported by [ 40 ], our findings demonstrate that the samples’ average value of 40 K under investigation is lower than the world average, while the average value of 226 Ra and 232 Th are higher than the world average concentrations [ 2 , 41 44 ]. The variations in the activity concentration are associated with the methods by which the soils are concentrated as well as the radioactive distribution in the rocks from which they arise.…”
Section: Resultssupporting
confidence: 61%
“…The current study showed that the distribution of uranium and thorium in the study rocks increases from basic to acidic types [ 35 ]. This trend may be attributed to the fact that in the early stages of magmatic evolution the principal minerals were pyroxenes, amphiboles, and plagioclase.…”
Section: Resultsmentioning
confidence: 99%
“…The U values estimate the first daughter isotope in the 238 U decay chain with the least amount of loss by utilizing the 234 Th energy peak (93 keV) to reflect the mass fraction of U. When 238 U and all of its daughter isotopes reach secular equilibrium, which takes place when the daughters’ rate of decay equals the parent’s one after four weeks, radium is measured at the 214 Pb peak of 352 keV energy, which is tied to a measure for the mass fraction of the U. Thorium is found in the Pb-212 peak, which has an energy of 238 keV [ 31 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Potassium, as well as its naturally occurring radioisotope 40 K, enters the plant roots through ion channels, or transporters, that are also used for the Cs + ion transporter. As a result, a high K content in soil inhibits the adsorption of Cs, and the impact could be heightened by higher mobility of the potassium ion in soil, which increases the availability of potassium to plants [17]. The purpose of this study was to provide information on: natural radionuclide activity concentrations in numerous medicinal plants; the radiation hazards related to the intake of therapeutic plants, as evaluated in this research.…”
Section: Introductionmentioning
confidence: 99%